First records of Madeira rockfish Scorpaena maderensis (Osteichthyes: Scorpaenidae) from the Tunisian coast (central Mediterranean) - Rafrafi-Nouira, Sihem (Array, 2018)
The authors present the first records of Madeira rockfish Scorpaena maderensis Valenciennes,1833 from the Tunisian coast (central Mediterranean). The specimens are described including morphometric measurements and meristic counts. The origin of the species in its new living area is discussed and commented. However, these new findings confirm the establishment of a viable population of S. maderensis in central Mediterranean.